2001
DOI: 10.1007/s004670100653
|View full text |Cite
|
Sign up to set email alerts
|

Combined pharmacotherapy for nocturnal enuresis

Abstract: Nocturnal enuresis is a common childhood disorder. Tricyclic antidepressants and anticholinergic agents have been the well accepted pharmacological treatment for this disorder and are efficacious in 40-70% and 10-50% of cases, respectively. The present study was performed to evaluate the effect of a combined treatment of tricyclic antidepressant and an anticholinergic agent. Twenty-two children aged 6-12 years with primary monosymptomatic nocturnal enuresis who did not prefer to use a conditioning alarm were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Combination of different therapies may also be instituted, especially in treatment of resistant cases (Table 1). Prescribing tricyclic antidepressants in conjunction with anticholinergics, 38 alarm therapy plus desmopressin acetate, 39 and bladder training plus an anticholingergic 40 are 3 such examples of combination therapy. DeWachter et al 40 found that administering oxybutinin along with a program of retention control training (RCT) or daily water loading to the point of urgency may improve enuresis by increasing bladder capacity and stimulating self-awakening in a small subset of patients with refractory symptoms.…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of different therapies may also be instituted, especially in treatment of resistant cases (Table 1). Prescribing tricyclic antidepressants in conjunction with anticholinergics, 38 alarm therapy plus desmopressin acetate, 39 and bladder training plus an anticholingergic 40 are 3 such examples of combination therapy. DeWachter et al 40 found that administering oxybutinin along with a program of retention control training (RCT) or daily water loading to the point of urgency may improve enuresis by increasing bladder capacity and stimulating self-awakening in a small subset of patients with refractory symptoms.…”
Section: Combination Therapymentioning
confidence: 99%
“…References: Physicians' Desk Reference,41 2003; The Harriet Lane Handbook,42 1996; Kaneko et al,38 2001.…”
mentioning
confidence: 99%
“…If no clear etiology is determined, there are several potential interventions that may abate the fre-quency of nighttime wetting. 12,13,15 Hormonal therapy with desmopressin has been shown to significantly reduce urine volume in some children with nighttime wetting, 14 despite the lack of consistent levels of nighttime antidi-uretic hormone levels in children with nighttime wetting. This may entail a reward system, and increasing the responsibility of the child by having him/her change the wet sheets.…”
Section: Nighttime Enuresis: Diagnosis and Managementmentioning
confidence: 99%
“…Other options include imipramine, which often reduces nighttime wetting for unknown reasons. 12,13,15 Hormonal therapy with desmopressin has been shown to significantly reduce urine volume in some children with nighttime wetting, 14 despite the lack of consistent levels of nighttime antidi-uretic hormone levels in children with nighttime wetting. 11 Finally, although hypnotherapy has been shown to reduce nighttime enuresis in some children, psychotherapy has not been shown to have any significant effect.…”
Section: Nighttime Enuresis: Diagnosis and Managementmentioning
confidence: 99%
“…16 Another study showed that combined treatment with a tricyclic antidepressant and an anticholinergic reduced monosynaptic nocturnal enuresis by 90.9% after 6 months of drug administration; combination therapy was more effective than monotherapy with either drug. 17 De Grazia and Cimador administered a combination of desmopressin and oxybutinin to children with enuresis and voiding disturbance and found that 93.2% had recovered after 6 months. 18 A positive response to treatment was also observed in 65.25% of patients with urodynamically demonstrated detrusor hyper-reactivity treated with oxybutinin and imipramine.…”
Section: Acupressure For Treating Enuresismentioning
confidence: 99%